Serum Uric Acid Level in Unipolar and Bipolar Depression - Gülçin Elboğa; Muhammet Berkay Özyürek; Zeynel Abidin Sayıner; Şengül Kocamer Şahin; Abdurrahman Altındağ (Medical Laboratory Technology Journal, 2019)
The purinergic system plays a role in the regulation of mood, motor activity, cognitive function, sleep, and behavior. Purinergic mechanisms can also play a role in various neuropsychiatric diseases. The objective of this study is to assess whether uric acid levels in patients with unipolar and bipolar depression are different in comparison to healthy controls and to determine the clinical parameters that can be associated with the uric acid level. This retrospective study consisted of 31 patients with major depressive disorder and 31 patients with bipolar disorder depressive episode and 31 healthy control subjects. The mean serum uric acid levels were found as follows: major depression patient group 4.56 (± 1.53) mg/dL, bipolar depression patient group 5.38 (± 1.43) mg/dL and control group 4.86 (± 1.56) mg/dL. There was no significant difference between patients and the control groups in terms of serum uric acid levels (P=0.075). Serum uric acid levels do not differ significantly in bipolar and unipolar depression. Also, there was no difference between patients and control. Therefore, studying the uric acid metabolism in major depression and bipolar disorder depressive episode according to the symptom severity with larger sample groups is suggested.